The model of formation of intracorporate system of project risk management in electronics - G. M. Kazanskiy (Путеводитель предпринимателя)
In this article the current state of Russian electronics is described, the main problems of its development are identified, the necessity of activation of innovative activity to create high technology electronic equipment is substantiated, a model of the formating intracorporate system of project risk management is developed.